MODEL PEMANFAATAN DANA ZAKAT UNTUK PENGEMBANGAN START-UP HALAL BERBASIS EKONOMI KREATIF DI INDONESIA - Nurhalifah Nurhalifah (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2025)
This study discusses the potential, role, and conceptual model of utilizing productive zakat funds integrated with creative economy principles as a strategy for empowering the economy of the Muslim community. Zakat not only functions as a social distribution instrument but also has great potential to promote economic independence through strengthening the creative sector and halal start-ups. Zakat institutions act as facilitators and catalysts in connecting zakat funds with creative entrepreneurs through financing, training, and sharia-based mentoring. The main challenges lie in managerial aspects, inter-institutional collaboration, and the digital literacy of mustahik (zakat recipients). This study uses a qualitative-descriptive approach with a conceptual research design based on library research. This study offers a conceptual model of “Creative Baznas Hub” based on four main pillars, namely innovation, collaboration, empowerment, and sustainability. This model aims to create a synergistic ecosystem between zakat institutions, the government, and the creative industry to produce sustainable socio-economic impacts. The results of the study show that the integration of zakat with the creative economy can strengthen the sharia economy, expand employment opportunities, and support the achievement of sustainable development goals (SDGs).